¿Cómo piensan y viven los adolescentes su sexualidad? Resumen de una memoria de investigación - SANZ SÁNCHEZ, Andrea (Cuadernos de Trabajo Social, 2009)
The rate of unwanted pregnancy and the number of adolescent females who voluntarily decide to interrupt pregnancy have not stopped increasing. This is the message we get from the media but, how have we reached this point? This article presents the results of research that seeks to delve into this matter from a qualitative point of view. Getting into the attitudes and behaviour of a group of teenagers, the objective is to provide the reader with a clearer image of a reality that we only think we know using a theoretical-practical framework that will enable us to adopt adequate strategies to solve this social problem.
Keywords: Adolescence; Sexuality; Sexual behaviour; Sexual attitudes; Pregnancy; Abortion